2013
DOI: 10.1039/c3an01389h
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of microbial species and strains in coculture biofilms by multivariate analysis of laser desorption postionization mass spectra

Abstract: 7.87 to 10.5 eV vacuum ultraviolet (VUV) photon energies were used in laser desorption postionization mass spectrometry (LDPI-MS) to analyze biofilms comprised of binary cultures of interacting microorganisms. The effect of photon energy was examined using both tunable synchrotron and laser sources of VUV radiation. Principal components analysis (PCA) was applied to the MS data to differentiate species in Escherichia coli-Saccharomyces cerevisiae coculture biofilms. PCA of LDPI-MS also differentiated individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…92,94 For example, ns-LDPI-MS was used to probe a single bacterial biolm consisting of two genetically engineered strains of Escherichia coli grown on the same substrate under identical conditions, then analyzed in intact form. 95 10.5 eV photons ionized the (ns, UV) laser desorbed neutrals to obtain the mass spectrum shown in Fig. 5(a).…”
Section: Ld Combined With Postionization Of Neutralsmentioning
confidence: 99%
See 1 more Smart Citation
“…92,94 For example, ns-LDPI-MS was used to probe a single bacterial biolm consisting of two genetically engineered strains of Escherichia coli grown on the same substrate under identical conditions, then analyzed in intact form. 95 10.5 eV photons ionized the (ns, UV) laser desorbed neutrals to obtain the mass spectrum shown in Fig. 5(a).…”
Section: Ld Combined With Postionization Of Neutralsmentioning
confidence: 99%
“…Photon energy tunable VUV radiation available at synchrotron light sources has also been used for ns-LDPI analysis. 19,21,91,92,[95][96][97] Tunable VUV provides the distinct advantage of selectively ionizing different classes of compounds; a recent study of organic-mineral soil samples showed that tuning the VUV photon energy and the UV laser parameters allowed control of fragmentation of the organic analyte and enabled compounds identication with less ambiguity. 98 Overall, ns-LDPI does not display the interfering intense matrix peaks that appear in MALDI, permitting more useful information to be obtained from the low mass region (m/z < 300) of the spectra.…”
Section: Ld Combined With Postionization Of Neutralsmentioning
confidence: 99%
“…In addition, 7.9 eV single-photon ionization has been coupled to nanosecond laser desorption, enabling even molecules larger than 10 000 Da to be detected . Laser-based single-photon ionization has more recently been combined with femtosecond laser desorption (fs-LD) at the University of Illinois at Chicago (UIC) for MS imaging of molecular species in biofilms , with near-micrometer lateral resolution (as measured on test samples) .…”
mentioning
confidence: 99%
“…199203 Untargeted metabolomic analysis of combined versus axenic cultures enables the study of large numbers of microbial combinations. In contrast to the labor intensive and less informative comparative approaches which required manual comparison of chromatographic (often UV or TLC) data, recent metabolomics approaches including principal component analysis (PCA) and partial least-squares regression (PLS-DA) identifies molecular features on the basis of mass-to-charge ( m/ z) and retention time.…”
Section: Advances Towards Understanding Microbial Interactionsmentioning
confidence: 99%